2006
DOI: 10.1038/nrmicro1598
|View full text |Cite
|
Sign up to set email alerts
|

H-NS, the genome sentinel

Abstract: Two recent reports have indicated that the H-NS protein in Salmonella enterica serovar Typhimurium has a key role in selectively silencing the transcription of large numbers of horizontally acquired AT-rich genes, including those that make up its major pathogenicity islands. Broadly similar conclusions have emerged from a study of H-NS binding to DNA in Escherichia coli. How do these findings affect our view of H-NS and its ability to influence bacterial evolution?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
302
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(314 citation statements)
references
References 85 publications
10
302
0
2
Order By: Relevance
“…The horizontal transfer of complete genes raises the important issue of how the expression of these genes is regulated in the new host. H-NS protein, a pleiotropic repressor of transcription, has a key role in selective silencing of the transcription of large numbers of horizontally acquired AT-rich genes, including pathogenicity islands (Dorman, 2007). It was recently found that Rho termination is required to suppress similar silencing (Cardinale et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal transfer of complete genes raises the important issue of how the expression of these genes is regulated in the new host. H-NS protein, a pleiotropic repressor of transcription, has a key role in selective silencing of the transcription of large numbers of horizontally acquired AT-rich genes, including pathogenicity islands (Dorman, 2007). It was recently found that Rho termination is required to suppress similar silencing (Cardinale et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Both functions are compatible with the structures assumed by plectonemically coiled DNA superhelices. Although in a plectoneme H-NS can bridge the two component duplexes, the binding of the protein is nucleated on one strand by an A/T-rich sequence (Bouffartigues et al 2007;Lang et al 2007;Dorman 2007). H-NS binding can then spread to adjacent regions of similar base composition, forming a nucleofilament.…”
Section: H-ns Nucleoprotein Complexesmentioning
confidence: 99%
“…H-NS has long been regarded as a global modulator of gene expression in response to pH, temperature, osmolarity and growth phase [14][15][16]. A large proportion of Salmonella genes induced upon temperature shift from 25°C to 37°C are dependent on H-NS [17], an effect attributed to putative conformational changes in H-NS and reduced DNA binding.…”
mentioning
confidence: 99%